2018
DOI: 10.1093/ecco-jcc/jjx184
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Haematopoietic Stem Cell Transplantation (AHSCT) in Severe Crohn’s Disease: A Review on Behalf of ECCO and EBMT

Abstract: Despite the major recent progress in the treatment of Crohn's disease [CD], there is a subset of patients in whom the disease runs an aggressive course with progressive tissue damage requiring early and repeated surgical management. Increasing evidence supports sustained and profound improvement in gastrointestinal parameters and quality of life following high-dose immunosuppressive therapy and autologous haematopoietic stem cell transplantation [AHSCT] compared to standard therapy in this context. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 88 publications
0
32
0
2
Order By: Relevance
“…Since then, recent studies have increased the evidence base for autologous HSCT in some indications, including multiple sclerosis [167][168][169][170][171], systemic sclerosis [172][173][174][175], Crohn's disease [176][177][178] and systemic lupus erythematosus [179]. Disease-specific recommendations are increasingly available from the EBMT and other professional societies as the evidence base for autologous HSCT growth [180][181][182][183]. Allogeneic HSCT has been predominantly used in the paediatric setting [164], particularly in patients with refractory autoimmune cytopenia and juvenile idiopathic arthritis [184,185].…”
Section: Autoimmune Diseases (Ad)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, recent studies have increased the evidence base for autologous HSCT in some indications, including multiple sclerosis [167][168][169][170][171], systemic sclerosis [172][173][174][175], Crohn's disease [176][177][178] and systemic lupus erythematosus [179]. Disease-specific recommendations are increasingly available from the EBMT and other professional societies as the evidence base for autologous HSCT growth [180][181][182][183]. Allogeneic HSCT has been predominantly used in the paediatric setting [164], particularly in patients with refractory autoimmune cytopenia and juvenile idiopathic arthritis [184,185].…”
Section: Autoimmune Diseases (Ad)mentioning
confidence: 99%
“…Crohn's disease is a potential indication for autologous HSCT, but allogeneic HSCT is appropriate for monogenic forms of inflammatory bowel disease (e.g. interleukin-10 signalling defects, immunodysregulation polyendocrinopathy enteropathy X-linked syndrome, Wiskott-Aldrich syndrome or increasingly X-linked inhibitor of apoptosis deficiency] [182]. Allogeneic HSCT may result in longterm responses in severe juvenile inflammatory arthritis [185].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…Surgical resection may not be feasible or may be declined by the patient if it will result in a permanent stoma. 6 Initial case series and single-centre cohort studies suggested that aHSCT could induce sustained clinical benefit. To date there has only been one randomised controlled trial to assess the value of aHSCT in refractory CD, the ASTIC trial 18 (see Table 3 ).…”
Section: Crohn's Diseasementioning
confidence: 99%
“…Significantly, the majority of patients who relapsed after aHSCT subsequently responded to reintroduction of anti-TNF therapy. 6,20 Further research is required to assess the place of aHSCT in the management of patients with treatment refractory and poor prognosis CD. ASTIClite is an NIHR-funded randomised controlled trial that will assess the benefit and risks of a low intensity mobilisation and conditioning HSCT regimen compared to the best currently available medical care in patients with significant CD refractory to at least two classes of biologic therapy.…”
Section: Crohn's Diseasementioning
confidence: 99%
“…Snowden et al publicó resultados similares a los descritos, en los que la carga de efectos adversos tras el TPHA era alta. Sin embargo, los pacientes respondían mejor a la terapia convencional que había sido suspendida previa al trasplante y a la que eran refractarios en un principio (28). Otros ensayos, como el de Lindsay et al recogen resultados de efectos adversos frecuentes y graves tras el trasplante como la muerte de un paciente por síndrome sinusoidal (29).…”
unclassified